Implementasi Pemahaman Orang Muda Katolik Tentang Kitab Suci Deuteurokanonika Bagi Kerukunan Di Naibonat, Kuasi Paroki Raknamo, Kupang - Abatan, Yofince; Bele, Graciana Amanda; Bria, Florens Maxi Un (Metta : Jurnal Ilmu Multidisiplin, 2024)
Young Catholics (OMK) are the next generation of sources of the Catholic faith. One of them is the holy book. In the Naibonat quasi-parish, OMK is very active in church activities. However, in reality, there are still many OMK who do not have adequate knowledge and understanding of the holy books, both deuteurocanonical. So, when a new translation of the deuteurocanonical holy book was published, OMK became confused about which holy book to have. This research aims to determine the extent of understanding of OMK in Naibonat regarding the deuterocanonical holy book, efforts that need to be made to increase OMK's understanding so that harmony is maintained through the teachings of the deuterurocanonical holy book. The method used is a descriptive qualitative method. Data collection techniques are interviews, observation and documentation combined with literary studies. The data obtained was reduced and analyzed so that it answered the research objectives. As a result, OMK in Naibonat do not understand the differences between Catholic and Protestant holy books. However, OMK knows that the contents of the holy book teach about helping each other and loving each other. This is also what is taught in deuteurocanonical books, such as in the book of Tobit which contains life advice for his son Tobiah to continue doing good, abstain from sin, and continue to help others by giving alms. Advice for OMKs like this is what encourages the creation of a harmonious life where by helping and loving each other, differences and diversity will not become obstacles but become tools that maintain harmony in life for the common good. The results of this research will be a starting point for community service activities in the form of socializing the deuteurocanonical holy book for OMK in Naibonat in particular and in the Archdiocese of Kupang in general.